To subtract \( 4.66 \times 10^{-5} - 7.34 \times 10^{-7} \), we first need to express both numbers with the same exponent.
The number \( 4.66 \times 10^{-5} \) can be rewritten as:
\[ 4.66 \times 10^{-5} = 4.66 \times 10^{-5} \times \frac{100}{100} = 4.66 \times 10^{-5} = 46.6 \times 10^{-6} \]
Now, we can rewrite \( 7.34 \times 10^{-7} \) as:
\[ 7.34 \times 10^{-7} = 0.0734 \times 10^{-6} \]
Now we can perform the subtraction:
\[ 46.6 \times 10^{-6} - 0.0734 \times 10^{-6} = (46.6 - 0.0734) \times 10^{-6} = 46.5266 \times 10^{-6} \]
Finally, we convert \( 46.5266 \times 10^{-6} \) back to scientific notation:
\[ = 4.65266 \times 10^{-5} \]
Thus, the result of the subtraction is:
\[ 4.65266 \times 10^{-5} \]
If we round it to four significant figures, we get:
\[ 4.653 \times 10^{-5} \]
However, it looks like none of the provided responses match this result, so please review the options.